PENGARUH RETURN ON ASSET, CURRENT RATIO, DEBT TO EQUITY RATIO, DAN ARUS KAS OPERASI TERHADAP HARGA SAHAM - Naomi Hesti Permatasari Suwanda; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study analyzes the effect of Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Operating Cash Flow on the stock prices of real estate and property companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This quantitative research uses secondary data obtained from annual financial statements and applies multiple linear regression analysis. The results indicate that, based on the model feasibility test, all four variables collectively influence stock prices. Partially, Return on Assets, Debt to Equity Ratio, and Operating Cash Flow have a significant effect on stock prices, while the Current Ratio does not have a significant effect.